Report of the Steering Committee on Science and Technology for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
The report provides a detailed approach to enhancing science and technology (S&T) in India during the Tenth Five Year Plan (2002-2007). It underscores the need for S&T to significantly contribute to societal benefits, aiming for economic growth and improved quality of life. Overall, these cooperative efforts aim to enhance India’s S&T landscape, addressing both national and global challenges through shared knowledge and resources. The long-term goal is sustainable socio-economic development through effective international partnerships. It also outlines the initiatives of the Council of Scientific and Industrial Research (CSIR) and key programs from the Tenth Five-Year Plan aimed at enhancing technology and research in various sectors in India.
Government of India Planning Commission
Government of India Planning Commission
Keywords: National Laboratories; Human Resource Development; Intellectual Property Management; New Millennium Technology Initiatives; Infrastructure Renovation; Biotechnology; Environment & Energy; Aerospace; Electronics; Healthcare; Public Partnership